2022
DOI: 10.1038/s41467-022-33221-z
|View full text |Cite
|
Sign up to set email alerts
|

The material properties of a bacterial-derived biomolecular condensate tune biological function in natural and synthetic systems

Abstract: Intracellular phase separation is emerging as a universal principle for organizing biochemical reactions in time and space. It remains incompletely resolved how biological function is encoded in these assemblies and whether this depends on their material state. The conserved intrinsically disordered protein PopZ forms condensates at the poles of the bacterium Caulobacter crescentus, which in turn orchestrate cell-cycle regulating signaling cascades. Here we show that the material properties of these condensate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
60
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 97 publications
(112 reference statements)
4
60
0
Order By: Relevance
“…Yet experiments show that a crowded environment can influence the appearance of pathological fibrillar states within biomolecular condensates. [68][69][70][71] It has also been found that the material properties of BCs are important for their cellular functions, [34,37] and disordered protein domains can exert steric pressure on cellular membranes. [72] Predicting the response of condensed phases of IDPs to the crowdedness of their environment is an important step in understanding their functions in health and possible role in treating diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet experiments show that a crowded environment can influence the appearance of pathological fibrillar states within biomolecular condensates. [68][69][70][71] It has also been found that the material properties of BCs are important for their cellular functions, [34,37] and disordered protein domains can exert steric pressure on cellular membranes. [72] Predicting the response of condensed phases of IDPs to the crowdedness of their environment is an important step in understanding their functions in health and possible role in treating diseases.…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31] A better understanding of how BCs are coupled (or not) to their crowded environment would assist in deciphering their cellular roles and constructing synthetic BCs. [32][33][34][35][36][37][38] The complexity of living cells has driven research on model condensates, which typically use unphysiologically-high concentrations of one, or at most a few, species of IDP in buffer, although their relevance to living cells has been strongly questioned. [39,40] An example is provided by in vitro experiments on the protein Fused in Sarcoma (FUS), an RNA-binding protein that is implicated in the neurodegenerative disease ALS.…”
Section: Introductionmentioning
confidence: 99%
“…Its N‐terminal region binds clients through a short conserved helix (Holmes et al, 2016 ; Nordyke et al, 2020 ). The central region of PopZ is disordered with many prolines and negatively charged amino acids and likely acts as a tuner of PopZ material properties (Lasker et al, 2022 ). Self‐assembly is mediated by interactions between three helices at the C‐terminal helical region (Figure 2a,b ; Bowman et al, 2010 ; Bowman et al, 2013 ; Laloux & Jacobs‐Wagner, 2013 ; Lasker et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Bio-polymer networks are ubiquitous in nature and play a vital role in (liquid-liquid phase separated) biomolecular condensates [1][2][3][4][5] and natural silk [6,7], as well as in artificial condensates [8] and novel soft materials such as hydrogels [9]. Reversible networks are typically constituted of intrinsically disordered protein (IDP) chains with 'sticker' patches that form intermolecular crosslinks, and 'spacer' sequences that covalently link the stickers within each protein chain.…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, in different species of algae the binding components vary in amino acid sequence [17], which suggests pyrenoids may be optimised for different environmental conditions. Molecular design parameters are the sticker binding affinity, the flexibility of the spacers, and the sequence of the chains [8], and will affect the local structure around the rubisco holoenzyme, as depicted in Figure 1.…”
Section: Introductionmentioning
confidence: 99%